Solid gold murder - Byron, Ellen (Byron, Ellen. Golden Motel mystery, 2025)
"With the summer season looming, former Hollywood sitcom writer Dee Stern has one small goal -- scrubbing her motel's unflattering moniker as the "Murder Motel." Dee and ex-husband-turned-business-partner Jeff Cornetta are excited to introduce a family-friendly panning activity complete with fool's gold just in time for the peak tourist months. Except neither could have anticipated the discovery of a real gold nugget or the ensuing social media frenzy. In a flash, the viral sensation draws grizzled prospectors, wide-eyed adventurers, and trend-chasing thrill seekers to the abandoned mines scattered around the woods . . . The instant popularity proves great for business, but it also attracts a group of out-of-touch Silicon Valley techies with dreams of striking it rich -- again. Dee finds herself particularly annoyed by the insufferably smug Sylvan Burr, a retired CEO who sold his startup before age 30 and won't let anyone forget it. But things take a sinister turn when Sylvan meets a grim fate at the bottom of a mineshaft, leaving Dee at the center of a deadly mystery that could end her days as a motelier. And while Sylvan had plenty of enemies, Dee suddenly faces adversaries rooting against her own success. Now, with her life and the future of the Golden Motel hanging by a thread, Dee must unearth a minefield of suspects and outwit a greedy killer before she finally digs herself too deep . . ."--